Performance of saccharomyces cerevisiae to acid stress in the alcoholic fermentation process (Research, Society and Development, 2021)
Yeasts are essential for an efficient fermentation process in the production of some foods and beverages. Fermentation’s effectiveness depends on several factors, including the pH of the medium. The wort acidity and the fermentative microorganism are closely linked, therefore, it is considered that the ideal pH for a satisfactory fermentation must be between 4.0 and 5.0. So, the work aimed to verify the performance of the saccharomyces cerevisiae yeast, when used in the production of alcoholic fermented in an acid stress medium. For this, tropical fruit were use as raw material for alcoholic fermentation, whose wort pH were outside the proper operating range. At end, the alcoholic fermented produced were analyzed for their physicochemical characteristics and the acceptance analysis was carried out through sensory analysis. The results showed that the fermented produced are within the standards foreseen in the legislation and present good acceptability by sensory analysis, from which it can be concluded that the yeast used is effective in its fermentative activity even when exposed to acid stress.